Initial underpricing and the Lisbon Euronext-listed companies - Isola, M. (2014)
This study aims to determine the level of initial underpricing in the Euronext Lisbon-listed companies during a period (1990 - 2010) that includes the effects of the current global financial crisis. We employed two methods of analysis: one for the short-term (i.e. the market adjusted abnormal returns (MAAR)), and the other for the long-term (i.e. the buy-and-hold abnormal returns (BHAR)). The results suggest the existence of low efficiency in the Portuguese stock market, generating underpricing for Initial Public Offerings (IPOs) in the short-term with positive MAARs. The same situation occurs for the long-term, where companies present positive BHARs.